Jewish identities : nationalism, racism, and utopianism in twentieth-century music - Móricz, Klára, 1962- (California studies in 20th-century music, 2008)
'Jewish Identities' mounts a challenge to prevailing essentialist assumptions about 'Jewish music', which maintain that ethnic groups, nations or religious communities possess an essence that must manifest itself in art created by members of that group.